Pemanfaatan Internet of Things untuk Monitoring Deteksi Tanah Longsor - Danang Setiya Raharja; Soepriyono; Andaryati; Nia Saurina; Aris Setiawan Indras Pratama (Faculty of Engineering, Universitas Serambi Mekkah, 2024)
Landslides are one of the most common natural disasters in Indonesia. This disaster can cause significant material losses and casualties. Therefore, a landslide monitoring system must be an early warning system. Prevention is one of the important steps to reduce the negative impact of landslides. The existing landslide early warning system still needs improvement, including low accuracy and slow response in providing information. This research aims to create a product, which we have named DinSor, as a landslide early warning system by utilizing the Internet of Things (IoT). The proposed system uses IoT-based sensors to detect changes in ground conditions, including soil movement through ultrasonic sensors and the degree of soil water content through soil mixture sensors. The data generated by these sensors is then displayed on the website as graphs and numbers for analysis. The trial results show that the developed system has advantages in detecting potential landslides. The system's response in providing information has also proven to be accurate and precise, with warning times shorter than previous systems. When the sensor indicates a potential landslide, a warning message can be sent to the local regional disaster management agency via WhatsApp.